2009
DOI: 10.1097/ccm.0b013e31819b629d
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prediction potential of an in silico computer model of intracranial pressure dynamics*

Abstract: The protocol for collecting physiologic data in subjects with severe TBI was feasible. The in silico ICP model with session-specific parameters accurately reproduced observed ICP response to changes in head-of-bed and respiration rate. We demonstrated modest success at predicting future ICP within a session and to a lesser extent between sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Models developed by Ursino and his team included multiple aspects of cerebral autoregulation, calibrated with data from a prospective study in which patients were given mild ventilation challenges (Ursino et al, 2000), and showed excellent prediction potential. Wakeland et al (2009) also calibrated a systems dynamics ICP model on patient data collected prospectively for pediatric TBI patients. In this model, patients were given mild physiologic challenges (raising or lowering the head of the bed or moderately adjusting ventilator settings) at multiple time points, but results revealed inadequate clinical prediction capability due to patient responses to a dramatically varying stimulus.…”
Section: Acute Injury Mechanismsmentioning
confidence: 99%
“…Models developed by Ursino and his team included multiple aspects of cerebral autoregulation, calibrated with data from a prospective study in which patients were given mild ventilation challenges (Ursino et al, 2000), and showed excellent prediction potential. Wakeland et al (2009) also calibrated a systems dynamics ICP model on patient data collected prospectively for pediatric TBI patients. In this model, patients were given mild physiologic challenges (raising or lowering the head of the bed or moderately adjusting ventilator settings) at multiple time points, but results revealed inadequate clinical prediction capability due to patient responses to a dramatically varying stimulus.…”
Section: Acute Injury Mechanismsmentioning
confidence: 99%